Pemanfaatan Kotoran Sapi Dalam Perspektif Hukum Islam - Jofani, Firman (Jurnal Ilmiah Ekonomi Islam, 2026)
The utilization of cattle manure as organic fertilizer and biogas energy has increasingly developed within the framework of sustainable agriculture and environmental management. Nevertheless, this practice raises juridical debates in Islamic law, as cattle manure is classified as a najis (impure) substance. This study aims to analyze the legal status of cattle manure utilization from the perspective of Islamic jurisprudence (fiqh muamalah) by examining Qur’anic verses, prophetic traditions, legal maxims, and the opinions of the four Sunni schools of law, particularly concerning impurity, utility (manfa‘ah), and public interest. This research employs a qualitative normative juridical approach through library research of classical and contemporary Islamic legal literature as well as environmental regulations. The findings indicate that the non-consumptive use of cattle manure, such as for fertilizer and biogas, is legally permissible (mubāḥ) provided that it does not involve human consumption, cause harm, and is properly managed. Moreover, when aimed at environmental protection and social welfare, such utilization may attain a recommended (mandūb) status in line with the principles of maṣlaḥah and maqāṣid al-sharī‘ah.